Ecologia comportamental de interações entre boto-cinza, Sotalia guianensis (van Béneden, 1864) (Cetacea: Delphinidae) e embarcações no litoral Paranaense - Oliveira, Aliny Gaudard (2011)
In Brazil, economic growth causes rapid increases in marine transports. The impact of this increase on marine mammals, combined with the lack of legal enforcement, is potentially dangerous. Knowledge of vessel-dolphin interaction is essential to Brazilian marine ecology. The study of dolphin behavior can identify problems and support actions for conservation. Our principle aim was to study vessel-dolphin interactions and determine whether group and infant behaviors were being affected. Observations (600hs) were conducted in Pontal do Paraná and Guaraqueçaba (Southern Brazil), in 2010. We used a mixed method of \"focal-group sampling\" and \"sequential sampling\" for behavior records. Boats were classified according to engine type: central (diesel) and outboard (petrol). Interactions were classified into positive, neutral and negative based on observed behaviors before, during and after vessel passage (947 events were recorded). The dolphins behavioral responses varied according to the engine type, speed and distance. Results showed increased frequency of neutral interactions when the observed distance between boats and dolphins was greater than 100m with vessel at low speed (0.1 to 2.0 km/h). The neutral and positive interactions were more frequent with center engine boats, probably because these vessels do not reach high speed (faster than 5km/h). All vessel types changed the dolphin s behaviors in some way. The distance between boats and dolphins influences the animal s surface behavior when interaction occurred with central motor vessels in Guaraqueçaba (z =- 5105, p= 0.000) and with outboard boats in Pontal (z = -3682, p =0.000) and Guaraqueçaba (z =- 3931, p = 0.000). The variable speed influenced surface behavior when interaction occurred with outboard boats in Guaraqueçaba (z = 2,107, p = 0.035). Changes in group structure, after vessel passage, such as mother and calve separation were observed, especially when the boat split the group. These data will contribute to human activities management in the region.